Not what to wear? Employers' liability for dress codes?. Issue 1 (March 2018) - Middlemiss, Sam
This article argues that in the United Kingdom currently there is a lack of an effective legal basis for challenging the imposition by employers of unfair or discriminatory dress codes in the workplace on employees or workers. Given the breadth of this topic, it will not be possible to also consider appearance or grooming standards such as outlawing beards or banning piercings or tattoos. Also consideration will be restricted to the aspects of discrimination which are contentious or most affected by dress codes or have not been dealt with in detail elsewhere namely sex and transgender discrimination. It is sadly the case that there is often uncertainty on the part of both employers and employees about when dress codes are acceptable or not and this should be addressed. There have been a number of research studies and legal cases highlighted recently which make this article timely. The cases tend to support the employers managerial prerogative to impose dress restrictions. Of recent interest is an incident where a woman was sent home from work on her first day for not wearing high heels which caused a public outcry, of which, more later. Clearly dress codes are often contentious and can lead to the discontent of employees and workers. In the absence of adequate legal protection in the United Kingdom, this article will examine what steps should be taken by management and legislators to deal with the problem of dress codes.